Pengaruh Motivasi, Self Awareness Dan Komunikasi terhadap Disiplin Kerja Karyawan di Perusahaan Daerah Air Minum (Pdam) Kabupaten Ponorogo - Fitriana Fitriana; Umi Farida; Tegoeh Hari Abrianto (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to determine the effect of motivation, self awareness and communication on the work discipline of employees in the Regional Water Supply Company (PDAM) of Ponorogo Regency. The location of research in Pramuka Street Number 21, Nologaten, Ponorogo Regency. The population in this study was 102 employees. The sample in this study used 50 respondents. Data collection techniques using questionnaires, then tested with validity and reliability test, while the method of data analysis using multiple regression analysis with the help of SPSS and hypothesis testing partially or simultaneously. The results showed that; (1) Motivation partially influences the work discipline of employees in the Regional Water Supply Company (PDAM) of Ponorogo Regency with a regression coefficient of 0.317, t value of 2.903 t table of 2.012 and sig. of 0.006 0.05, (2) Self Awareness partially influences the work discipline of employees in the Regional Water Supply Company (PDAM) of Ponorogo Regency with the results of the regression coefficient of 0.409, t value of 3.478 t table of 2.012 and sig. of 0.001 0.05, (3) Communication partially influences the work discipline of employees in the Regional Water Supply Company (PDAM) of Ponorogo Regency with the results of a regression coefficient of 0.310, t value of 2.178 t table of 2.012 and sig. of 0.035 0.05, (4) Motivation, self awareness and communication simultaneously affect employee work discipline in the Regional Water Supply Company (PDAM) of Ponorogo Regency with the calculated F value of 14.807 F table 2.81 and sig value. of 0,000 0.05, (5) Self awareness is the most dominant variable affecting the work discipline of employees in the Regional Water Supply Company (PDAM) of Ponorogo Regency with the result of self awareness variable t value of 3.478 is greater than the value of t variable count motivation and communication variables. Furthermore, from the value of sig. the variable self awareness of 0.001 is smaller than the value of sig. motivation variable and communication variable.